From awareness to action: e-waste handling practices among medical students in Puducherry - Katole, Ashwini; Jha, Anupriya; Giri, Purushottam; Karpaga, Priya P.; Shukla, Arvind K. (International Journal Of Community Medicine And Public Health, 2026)
Background: Given the global concern over e-waste, which means discarded electrical or electronic devices, it makes sense that many families would be interested in recycling their old appliances. Today, India is one of the largest producers, but we still have a huge gap in safe recycling and disposal. This study aimed to evaluate the awareness and practices of e-waste management among medical students in Pondicherry with changing national policies and global trends. Methods: A cross-sectional study was carried out for three months, among the students from the second year to final year (n=401) of two randomly selected medical colleges in Pondicherry. Data regarding awareness and practice were collected by a pre-designed semi-structured questionnaire, and data were analyzed using Microsoft EXCEL and Epi Info. Results: The study defined the respondents of our findings as being 85.8% aware of the term “e-waste” and 91.0% acknowledging the e-waste’s environmental hazards. In addition, only 12.2% had ever heard of the Indian laws concerning e-waste protection and its management. Less than 10% of the respondents reported always setting aside e-waste for recycling. Males were better informed of the amount of waste and what could be separated, such as guidelines classification, while females better acknowledged the consequences associated. Conclusions: University students’ knowledge of medical schools on e-waste policy is limited, and safe disposal practice may not reflect their awareness of the risk. Medical school inquiry-triggered education, directly connected to formal recycling systems, could bridge the gap between perceived risk and action.